Raquel de Toledo - López Aranda, Juan Ricardo 1934-1996; Fandino, Roberto ([España] : Televisión Española, 1995)
Escenificación de la historia de Alfonso VIII y su amante judia llamada Raquel.
Keywords: ESPAÑA -- HISTORIA